2015
DOI: 10.1038/nmat4348
|View full text |Cite
|
Sign up to set email alerts
|

Brownian diffusion of a partially wetted colloid

Abstract: The dynamics of colloidal particles at interfaces between two fluids plays a central role in microrheology, encapsulation, emulsification, biofilm formation, water remediation and the interface-driven assembly of materials. Common intuition corroborated by hydrodynamic theories suggests that such dynamics is governed by a viscous force lower than that observed in the more viscous fluid. Here, we show experimentally that a particle straddling an air/water interface feels a large viscous drag that is unexpectedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
138
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(149 citation statements)
references
References 34 publications
11
138
0
Order By: Relevance
“…For spherical colloids approximately one µm in diameter at oil/water interfaces, measurements of the surface diffusivity and drag from the Stokes-Einstein equation are in agreement [14,15] with continuum theory. But for these same particles at an air/water interface or nanometer sized particles at an oil/water interface, the surface diffusivity is smaller than would have been predicted from the Stokes Einstein equation using the continuum surface drag, or, paradoxically decreases with crossing into the gas or less viscous phase, becoming smaller than the bulk diffusivity [16][17][18][19][20]. Several mechanisms have been proposed to explain the unexpectedly low surface diffusivities.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…For spherical colloids approximately one µm in diameter at oil/water interfaces, measurements of the surface diffusivity and drag from the Stokes-Einstein equation are in agreement [14,15] with continuum theory. But for these same particles at an air/water interface or nanometer sized particles at an oil/water interface, the surface diffusivity is smaller than would have been predicted from the Stokes Einstein equation using the continuum surface drag, or, paradoxically decreases with crossing into the gas or less viscous phase, becoming smaller than the bulk diffusivity [16][17][18][19][20]. Several mechanisms have been proposed to explain the unexpectedly low surface diffusivities.…”
mentioning
confidence: 92%
“…Obviously, surfactant contaminants could give rise to viscous surface shear and Marangoni forces which increase the surface drag. However, in diffusion experiments in which tension measurements indicate a relatively clean interface, studies suggest that thermal fluctuations at the contact line can create forces on the particle [20]. In particular, the surface of colloids are typically not smooth, and the fluid interface can become pinned at heterogeneities causing hysteresis in the measurement of the contact angle [21].…”
mentioning
confidence: 99%
“…Recent experimental measurements of the (in-plane) diffusivity of microparticles at interfaces by Boniello et al 31 revealed that hydrodynamic drag models cannot explain the dissipative forces experienced by a particle straddling a liquid-fluid interface at different contact angles. Boniello et al proposed that thermal motion of the liquid interface can induce a dominant contribution to (in-plane) dissipative forces that can be estimated via the fluctuation-dissipation theorem.…”
Section: Introductionmentioning
confidence: 99%
“…Other work examines the effect of pinning on particle dynamics lateral to an interface. Recent experimental studies by Boniello et al [13] indicate that the lateral diffusion of colloidal particles at a fluid interface is likely slowed by transient pinning events. Sharifi-Mood and coworkers [14] showed that strong pinning can locally distort the interface around a colloidal particle, affecting how particles migrate on a curved surface.…”
Section: Introductionmentioning
confidence: 99%